Perspective on the clinical management of post-stroke aphasia and dysphagia using repetitive transcranial magnetic stimulation (rTMS) - Georgiou, Anastasios M. (My University, 2024)
Stroke, a prevalent cause of disability worldwide, presents individuals with a range of formidable challenges; notably aphasia, reported at rates of 7%−77% across high- and middle-income countries (1), and dysphagia, with incidence rates reaching up to 80% (2). Despite their distinct manifestations, these conditions are pivotal for survival, human communication, and overall quality of life (QoL) post-stroke. Within the domain of medical speech pathology, aphasia and dysphagia have historically been key areas of therapeutic intervention, primarily through behavioral therapies. However, the advent of technological advancements has fueled interest in exploring noninvasive brain stimulation techniques (NIBST), such as repetitive transcranial magnetic stimulation (rTMS), for their potential in leveraging neuroplasticity to address these post-stroke deficits.
Keywords: stroke; TMS; aphasia; methodological rigor; neurostimulation